Nasopharyngeal lymphomas: A case report - Ribeiro, Leandro (2014)
Introduction: Lymphomas are the second most common malignant neoplasm of the head and neck. Most cases 60 to 70% are located in the Waldeyer’s Ring, especially in the tonsils. Despite being less frequent, nasopharyngeal lymphomas usually represent a diagnostic challenge as their clinical presentation may mimic other nosological entities, distinct from the underlying pathology. Methodology: Case study of Mantle Cell Lymphoma (MCL) of the pharyngeal cavum, initially diagnosed as Acute Bacterial Rhinosinusitis. Results: Female, 80 years old, retired (former housemaid) with a condition of nasal obstruction, purulent rhinorrhea, autophony and a sensation of aural fullness with 3 weeks of evolution. No symptomatic improvement after antibiotic therapy. Complementary study detected a nasopharyngeal mass which, upon biopsy, was consistent with a Non-Hodgkin’s Mantle Cell Lymphoma. Complete tumour staging procedures revealed multiple cervical lymphadenopathy and bone marrow involvement (Ann Arbor Stage IV). The patient was subjected to 6 cycles of polychemotherapy according to the R-CHOP regimen (rituximab, cyclophosphamide, hydroxydaunorubicin, vincristine and prednisolone), with partial remission. Conclusion: The lymphoproliferative disorders of the nasopharynx integrate the differential diagnosis of rhinosinusitis, especially if associated with middle ear effusion.